2023
DOI: 10.1186/s12889-023-16176-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and environmental factors associated with waterpipe tobacco smoking among Iranian adults: a PERSIAN cohort-based cross-sectional study

Abstract: Background Waterpipe tobacco smoking (WTS) is associated with several deleterious health outcomes. We sought to estimate the prevalence of WTS and explore socioeconomic inequalities associated with this culturally-rooted tobacco smoking practice among Iranian adults. Methods A cross-sectional analysis was conducted among 20,460 adults (ages 18 and older) enrolled in the PERSIAN cohort study during 2020. Data were collected on socioeconomic status (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Overall, our results align with those from other studies that have found a statistically significant, positive association between cigarette smoking status, alcohol consumption status, or shisha smoking among family members or close friends and being a person who currently smokes shisha (4, 5, 45, 46). Other studies have also found a negative association between age and shisha smoking, with younger individuals being more likely to be people who currently smoked shisha than older individuals (1, 47). However, the three studies in Nigeria that have looked at age did not find any statistically significant relationship with shisha smoking status.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Overall, our results align with those from other studies that have found a statistically significant, positive association between cigarette smoking status, alcohol consumption status, or shisha smoking among family members or close friends and being a person who currently smokes shisha (4, 5, 45, 46). Other studies have also found a negative association between age and shisha smoking, with younger individuals being more likely to be people who currently smoked shisha than older individuals (1, 47). However, the three studies in Nigeria that have looked at age did not find any statistically significant relationship with shisha smoking status.…”
Section: Discussionmentioning
confidence: 91%
“…The remaining one was also in a different population, i.e., nightclub patrons (5). Many studies report that males are more likely to be people who currently smoke shisha than females (47, 48). However, as with our study, most studies in Nigeria have found no statistically significant difference between males and females in the likelihood of being a person who currently smokes shisha (4, 5, 20).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire included multiple items related to general information, socioeconomic status, employment history, physical activity, and smoking history. In this study, individuals classified as smokers were defined as those who reported a consistent smoking habit of at least one cigarette per day for a minimum duration of 1 month or those who had recently quit smoking, specifically within a month prior to their participation in the research ( Moghadam et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated a potential link between smoking and aging, with a noteworthy prevalence of smoking, particularly cigarette smoking, observed among the elderly population in Iran ( Huang et al, 2022 ; Vatankhah et al, 2020 ). Notably, a research has demonstrated a significant association between the prevalence of smoking, including waterpipe tobacco smoking, and age, as well as the presence of cardiovascular disease, among Iranian adults aged 35 to 70 ( Moghadam et al, 2023 ; Zahirian Moghadam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the latest study reported in 2023 from Iran, prevalence of waterpipe smoking was associated with socioeconomic inequalities and lifestyle factors among adults. This study, however, did not provide any information regarding waterpipe metrics, particularly in terms of frequency patterns between daily and occasional users ( 19 ).…”
Section: Introductionmentioning
confidence: 97%